2019
DOI: 10.1111/mpp.12866
|View full text |Cite
|
Sign up to set email alerts
|

SIGS vs HIGS: a study on the efficacy of two dsRNA delivery strategies to silence Fusarium FgCYP51 genes in infected host and non‐host plants

Abstract: Summary CYP3RNA, a double‐stranded (ds)RNA designed to concomitantly target the two sterol 14α‐demethylase genes FgCYP51A and FgCYP51B and the fungal virulence factor FgCYP51C, inhibits the growth of the ascomycete fungus Fusarium graminearum (Fg) in vitro and in planta. Here we compare two different methods (setups) of dsRNA delivery, viz. transgene expression (host‐induced gene silencing, HIGS) and spray application (spray‐induced gene silencing, SIGS), to assess the activity of CYP3RNA and novel dsRNA speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 51 publications
2
54
0
Order By: Relevance
“…Moreover, we found that the transferred SIGS-associated RNAs confer target gene silencing in the respective tissues as well as Fg disease resistance (Fig. 7, Koch et al, 2019). Interestingly, we measured the highest silencing efficiency in the tissue that was either directly sprayed or near to the sprayed locus.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, we found that the transferred SIGS-associated RNAs confer target gene silencing in the respective tissues as well as Fg disease resistance (Fig. 7, Koch et al, 2019). Interestingly, we measured the highest silencing efficiency in the tissue that was either directly sprayed or near to the sprayed locus.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to the generation of RNA silencing signals in planta , plants can be protected from pathogens and pests by exogenously applied RNA biopesticides (known as spray-induced gene silencing, SIGS) (for review see: Mitter et al 2017; Cai et al 2018; Dubrovina and Kiselev 2019; Gaffar and Koch 2019; Dalakouras et al 2020). Over the last decade, our research (Koch et al, 2013; 2016; 2018; 2019; Höfle et al, 2019, Werner et al, 2019) and the work of others have revealed the enormous potential of RNA-silencing strategies as a potential alternative to conventional pesticides for plant protection, regardless of how target-specific inhibitory RNAs are applied (i.e. endogenously or exogenously).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we discovered that longer dsRNAs of 400–800 nt exhibited a higher gene-silencing efficiency and a stronger disease resistance than 200-nt dsRNAs (Koch et al, 2019), indicating that the quantity of siRNAs derived from a longer dsRNA precursor is simply higher. To test whether the length and/or the selected target gene sequence influences silencing efficiencies, we constructed 10 different dsRNA constructs targeting FgAGO/FgDCL pairs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of how target-specific inhibitory RNAs are applied (i.e. endogenously or exogenously), the use of HIGS and SIGS technologies to control Fusarium species have been shown to be a potential alternative to conventional pesticides (Koch et al 2013; Ghag et al 2014; Cheng et al 2015; Hu et al 2015; Chen et al 2016; Pareek and Rajam 2017; Bharti et al 2017; Baldwin et al 2018; Koch et al 2018; Koch et al 2019), supporting the notion that RNAi strategies may improve food safety by controlling the growth of phytopathogenic, mycotoxin-producing fungi (reviewed by Machado et al 2017; Majumdar et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation